O Senai de Goiás no atual contexto da educação profissional e seus desafios e perspectivas - Pascoal, Elias (2009)
This Dissertação de Mestrado presents the results of a research that it intended to identify the effect of the process of globalization in the world of the work, in the creation of new professional demands, visualizing the new sphere where if it develops the binomial Education and Work in the goiano context, thus to analyze the challenges of the professional education and as the SENAI - GO has searched and possible ways for the current professional formation new. It took the professional education developed by the SENAI of Goiás and its conjunctural challenges, in order to answer as historically the SENAI-GO has faced these constant socioeconômicos, structural and educational challenges, taxes for the reality of the mutant scenes that today base the professional education. It searched to understand the legal apparatus of the professional education developed by the SENAI-GO, to perceive in its theoreticiandescription- philosophical referencial, the possible decurrent contradictions of its interpretation and application for, finally, pointing possible alternatives of confrontation of the challenges of the professional education in the State of Goiás. It was clearly the fact of that the deep changes in the world of the work reflected on the conception of the professional education, the aiding of chances the workers with bigger experience, escolaridade and ability, cause the problem of the increasing reduction of the work ranks - effect of the process of world-wide economic globalization. When investigating the possible ways of a professional education capable to form compatible professionals with the new demands of the world of the work, the process of implantation of the joint of average education and professional education was elencou technique of average level, to analyze itself as if it has constituted this process of joint, first in the experience lived in Catalan, the State College Netto João De Campos, in the course of Electromechanical, during the years of 2006 the 2008, and, later, the experience lived deeply in the City of Anápolis, in the College of Technology SENAI Robert Mange, in course since 2008, the Courses of Chemistry Industrial, of Electrotechnical and the Course of Electromechanical, of where if it concluded that the joint of average education with the professional education in the searched entities, not yet it was accomplished fully.